The Role of Tactile Stimulation for Expectation, Perceived Treatment Assignment and the Placebo Effect in an Experimental Nausea Paradigm - Aichner, Simone; Haile, Anja; Hoffmann, Verena; Olliges, Elisabeth; Tschöp, Matthias H.; Meissner, Karin (Frontiers in Neuroscience, 2019)
Introduction Tactile stimulation during a placebo treatment could enhance its credibility and thereby boost positive treatment expectations and the placebo effect. This experimental study aimed to investigate the interplay between tactile stimulation, expectation, and treatment credibility for the placebo effect in nausea. Methods Ninety healthy participants were exposed to a 20-min vection stimulus on two separate days and were randomly allocated to one of three groups on the second day after the baseline period: Placebo transcutaneous electrical nerve stimulation (TENS) with tactile stimulation (n = 30), placebo TENS without tactile stimulation (n = 30), or no intervention (n = 30). Placebo TENS was performed for 20 min at a dummy acupuncture point on both forearms. Expected and perceived nausea severity and further symptoms of motion sickness were assessed at baseline and during the evaluation period. At the end of the experiment, participants in the placebo groups guessed whether they had received active or placebo treatment. Results Expected nausea decreased significantly more in the placebo groups as compared to the no treatment control group (interaction day × group, F = 6.60, p = 0.003, partial η2 = 0.20), with equal reductions in the two placebo groups (p = 1.0). Reduced expectation went along with a significant placebo effect on nausea (interaction day × group, F = 22.2, p < 0.001, partial η2 = 0.35) with no difference between the two placebo groups (p = 1.0). Twenty-three out of 29 participants in the tactile placebo group (79%) but only 14 out of 30 participants (47%) in the non-tactile placebo group believed that they had received the active intervention (p = 0.015). Bang’s blinding index (BI) indicated random guessing in the non-tactile placebo group (BI = 0; 95% CI, −0.35 to 0.35) and non-random guessing in the direction of an “opposite guess” in the tactile placebo group (BI = −0.52; 95% CI, −0.81 to −0.22). Conclusion Tactile stimulation during placebo TENS did not further enhance positive treatment expectations and the placebo effect in nausea but increased the credibility of the intervention. Further trials should investigate the interaction between perceived treatment assignment, expectation, and the placebo effect during the course of a trial.